Socio-Cultural Dimensions in the Development of Indonesian Maritime Strength: Strengthening Maritime Identity and Resilience Archipelago Society - Saputra, Rizki Marman; Somantri, Gumilar Rusliwa; Subroto, Athor; Marsetio, Marsetio (Universitas of Muhammadiyah Makassar, 2024)
This study explores the integration of socio-cultural dimensions into Indonesia's maritime defense strategy, focusing on strengthening maritime identity and archipelagic community resilience. It aims to examine multifaceted aspects of maritime identity, identify traditional practices and resilience mechanisms, analyze preservation challenges, explore existing integration efforts, and develop a comprehensive socio-cultural framework for maritime defense. Employing a qualitative, exploratory approach with literature study as the primary data collection method, the research analyzes academic journals, books, and policy documents through thematic analysis and synthesis. Key findings reveal the multifaceted nature of Indonesia's maritime identity, encompassing historical, economic, social, and ecological dimensions. The study highlights the rich traditional ecological knowledge and resilience mechanisms of island communities, including sustainable resource management practices, adaptation strategies, and intergenerational knowledge transfer. Challenges such as urbanization, environmental degradation, cultural erosion, and socioeconomic inequality threaten the preservation of maritime identity and community resilience. The research also identifies existing initiatives successfully integrating socio-cultural elements into maritime strategies, such as community-based monitoring and participatory decision-making processes. The study concludes that Indonesia's maritime strength is intrinsically linked to its socio-cultural heritage and the resilience of its island communities. Integrating these elements into maritime defense strategies can enhance effectiveness, sustainability, and community engagement while preserving cultural identity. The proposed framework offers a holistic approach to maritime defense that harmonizes technological advancement with cultural preservation and community empowerment. This approach recognizes the symbiotic relationship between strategic planning, cultural heritage preservation, and sustainable development, paving the way for a more robust and culturally sensitive maritime defense strategy for Indonesia.